Communication Features Of Youth Public organizations Members - Yavorovska, Lyubov; Semenihina, K (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article discusses the research of communication features members of youth YGO. The basis of the study is the approach to the communication study of G. M. Andreeva, according to which communicative, interactive and perceptive components of communication are defied. The results of empirical studies have shown that there are signifiant differences in communication between members of a youth organization and young people who are not representatives of a youth organization.